Effect of a 4-week detraining period followed by a 4-week strength program on isokinetic strength in elite youth soccer players - Samolis, V.; Michailidis, Y.; Mandroukas, A.; Mikikis, D.; Gissis, I.; Metaxas, T. (Journal of Exercise Rehabilitation, 2019)
The aim of the present study was to determine if 4 weeks of training cessation (detraining) followed by a 4-week strength training program can affect the isokinetic strength of elite youth soccer players. There were 13 players who participated in the study. The players performed anthropometric measurements and lower limb isokinetic strength measurements 3 times, before the training cessation, after the training cessation and after the 4-week strength training program. No significant differences were observed in the anthropometric and strength measurements (P>0.05) after the detraining period and after the training program (P>0.05). These results indicate that 4 weeks of detraining in elite youth soccer players does not have any significant effects according to their anthropometric characteristics and isokinetic strength of their lower limbs. Furthermore, neither the 4-week training program affected the parameters above. Perhaps, youth players can maintain the benefits of training better than adults due to their neural adaptations. The duration of the strength training program could be the reason of the lack of adaptations.